Experiments in International Finance - Childs, Jason (My University, 2002)
This thesis contains three essays that are intended to be independent works. The essays all relate to applications of experimental methods to issues of international finance. The issues of experimental finance investigated are Rate of Return Parity and Currency Crises. The first essay investigates Rate of Return Parity using a laboratory environment in which two double auction asset markets are run simultaneously. Rate of Return Parity can then be used to predict the relative price of the assets in the two markets. The results of this experiment show that Rate of Return Parity is observed when assets are very similar and the exchange rate between the currencies in which the asset markets are denominated is perfectly fixed. The degree of Rate of Return Parity is reduced as the assets become dissimilar, or the exchange rate between currencies becomes unstable. The second essay employs robot asset traders to investigate some of the behavioural rules that subjects may have been using in the simultaneous asset markets of the first essay. The goal of the robot traders is to generate data that is qualitatively similar to that ofthe data generated in the experiment presented in the first essay. Ofthe various robot populations considered, profit maximizing robots that employ a weighted trend function in calculating the value of the asset combine with a single arbitrageur produce data that is most similar to that of human subjects. The third essay examines a laboratory environment in which a currency crisis is possible but not guaranteed. This was done using an environment similar to the one used to investigate Rate of Return Parity, with a fixed and known amount of reserves with which the fixed exchange rate would be defended. In the laboratory environment the exchange rate would change if the reserves fell to zero. In this manner whether or not there was a change in the exchange rate was completely under the control of the subjects. Results indicate that subjects are able to generate currency crises based on self-fulfilling prophecies. Overall the work of this thesis indicates that care should be taken when applying Rate of Return Parity to complex environments, and that the commitment of a central bank to defending a fixed exchange rate has an important role to play in determining if a currency crisis will occur.
Keywords: Economics; Economics